Analysis of Radiographer Requirements in the Radiology Department of Bhayangkara Hospital, Semarang - Rosidah, Siti; Jamil, Masfufatun; Suraningsih, Nanik (Jurnal EduHealth, 2025)
Radiology, as a supporting tool in establishing a diagnosis, must maintain the quality and quality of service. Therefore, it requires support from human resources.One of the human resources (HR) in the Radiology Installation is the radiographer. According to Minister of Health Regulation No. 24 of 2020 concerning clinical radiology services, the number of radiographers required for full-service, primary, and intermediate clinical radiology services is two people per unit. Meanwhile, for primary clinical radiology services, the requirement is one person per unit. According to the SNARS radiology accreditation success book, edition 1, the number of human resources required can be calculated based on the workload. The number of radiographers must be met to maintain the quality of service.This research aimsThe research was to determine the number of radiographers needed in the Radiology Installation of Bhayangkara Hospital.This research is a descriptive qualitative study. Data collection was conducted through observation, interviews, and documentation of hospital data. The data obtained will be processed and calculated to determine the number of radiographers needed in accordance with Minister of Health Regulation No. 24 of 2020 and SNARS Edition 1 of 2018. Subsequently, an analysis will be conducted to determine the number of radiographers needed.The results of the study show that the number of radiographers needed based on the equipment is 10, while based on the number of radiographers needed based on the equipment is 10.The workload is 24-hour service, divided into three shifts, totaling nine radiographers. Currently, the number of radiographers is sufficient, but Bhayangkara Hospital lacks human resources and administrative staff.The conclusion of the research is that there is a need to review the human resource needs in radiology installations to ensure they comply with standards